2022
DOI: 10.1111/ejh.13736
|View full text |Cite
|
Sign up to set email alerts
|

Mutation profiling of circulating tumor DNA identifies distinct mutation patterns in non‐Hodgkin lymphoma

Abstract: Non-Hodgkin lymphoma (NHL) is the most common hematologic malignancy worldwide, which encompasses three broad molecule categories including B-cell, T-cell, and natural killer (NK)-cell neoplasms. 1 Clinical manifestation and pathological features are highly heterogeneous across NHL subtypes, varying from the most indolent to the most aggressive malignancies. 2 It is known that etiologic heterogeneity of NHLs is associated with diverse risk factors and molecular mechanisms such as genomic alterations. 2,3 Targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
(44 reference statements)
0
6
0
2
Order By: Relevance
“…Some studies have reported that monitoring ctDNA can reflect treatment response, monitor disease progression, and facilitate prediction of prognosis in some solid cancers 39,41–43 . Recently, some research reported that ctDNA had prognostic value in lymphoma patients 25,27,44 . Our previous work had demonstrated that ctDNA assessment could predict the therapy response and monitor disease status in a noninvasive way in ENKTL 28 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have reported that monitoring ctDNA can reflect treatment response, monitor disease progression, and facilitate prediction of prognosis in some solid cancers 39,41–43 . Recently, some research reported that ctDNA had prognostic value in lymphoma patients 25,27,44 . Our previous work had demonstrated that ctDNA assessment could predict the therapy response and monitor disease status in a noninvasive way in ENKTL 28 .…”
Section: Discussionmentioning
confidence: 99%
“…39,[41][42][43] Recently, some research reported that ctDNA had prognostic value in lymphoma patients. 25,27,44 Our previous work had demonstrated that ctDNA assessment could predict the therapy response and monitor disease status in a noninvasive way in ENKTL. 28 The plasma ctDNA concentration was significantly correlated with the MTV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mature B-cell neoplasms comprise more than 80% of non-Hodgkin lymphomas and consist of different pathological subtypes with variable clinical outcomes [ 1 ]. Tumor tissue biopsies are the gold standard to analyze lymphoma genetic profiles, identifying useful mutations as molecular biomarkers [ 2 , 3 ]. Moreover, targeted next-generation sequencing (NGS) has contributed to reclassifying molecular subtypes of lymphomas through new algorithmic models.…”
Section: Introductionmentioning
confidence: 99%